Fe-based alloy ribbon and Fe-based amorphous alloy ribbon
Optimized Fe-based alloy compositions and controlled heat treatment methods stabilize fine crystal structures, addressing coarsening issues and enhancing magnetic properties and workability for industrial applications.
Patent Information
- Application Number
- JP2020156556
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-17
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-09-17
AI Technical Summary
Existing methods for producing Fe-based microcrystalline alloys face issues such as partial or widespread coarsening of crystal grains during heat treatment, leading to poor workability and reduced yield, especially when transitioning from an amorphous to microcrystalline state.
The composition of Fe-based alloys is optimized with specific ratios of elements like B, Si, Cu, Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, W, N, P, and S, along with controlled heat treatment conditions, to maintain a fine crystal structure and improve workability, using X-ray diffraction patterns to monitor grain size and prevent coarsening.
The solution results in Fe-based alloys with excellent soft magnetic properties and improved workability, suitable for applications like transformers and choke coils, with enhanced manufacturing yield and reduced defects.
Smart Images

Figure 0007610097000001 
Figure 0007610097000002 
Figure 0007610097000003
Abstract
Description
[Technical field]
[0001] The present invention relates to Fe-based alloy ribbon and This relates to Fe-based amorphous alloy ribbons. [Background technology]
[0002] The term "amorphous" as used here means, as described in Non-Patent Document 1, "amorphous is translated as 'unformed' or 'non-crystalline', but its definition is 'a substance in which the arrangement of atoms that make up the substance does not have the long-term regularity of crystals.'" (Non-Patent Document 1). Generally, amorphous materials are produced by methods such as rapid cooling of a melt, electrodeposition, vapor deposition, and sputtering.
[0003] As a method for continuously producing ribbon or wire by quenching an alloy from a molten state, the centrifugal quenching method, the single roll method, the twin roll method, etc. are known. In these methods, the molten metal is ejected from an orifice or the like onto the inner or outer peripheral surface of a metal drum rotating at high speed, whereby the molten metal is rapidly solidified to produce ribbon or wire. In addition, by appropriately selecting the alloy composition, it is possible to obtain an amorphous alloy similar to liquid metal, and to produce a material with excellent magnetic or mechanical properties.
[0004] Patent documents 1 and 2 report that a microcrystalline alloy with good magnetic properties can be obtained by crystallizing an amorphous alloy obtained by rapid solidification through heat treatment. These microcrystalline alloys have characteristics such as high magnetic permeability, low magnetostriction, and low coercive force, and can be used in various transformers, choke coils, noise suppression parts, etc.
[0005] There is a correlation between the structure and magnetic properties of fine crystal materials. For example, Non-Patent Document 2 describes the relationship between the crystal grain size D and coercive force Hc of Fe as follows: when the crystal grain size D is reduced, in the region where the crystal grain size D is greater than 600 Å (60 nm), Hc increases inversely proportional to the crystal grain size D as the crystal grain size D decreases, but in the region where the crystal grain size D is smaller than 600 Å (60 nm), Hc increases by the sixth power of the crystal grain size (D 6) It has also been reported in Patent Document 2 that the preferred average grain size for exhibiting excellent soft magnetic properties in an Fe-based soft magnetic alloy is 500 Å (50 nm) or less, and more preferably 200 Å (20 nm).
[0006] Recently, Patent Document 3 reports a method of obtaining a nanocrystalline soft magnetic alloy that has both magnetic properties and handleability by heat treating an initial ultrafine crystal alloy having fine crystal nuclei. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Unexamined Patent Publication No. 64-79342 [Patent Document 2] Japanese Patent Application Publication No. 1-156451 [Patent Document 3] International Publication No. 2008 / 133301 [Non-patent literature]
[0008] [Non-Patent Document 1] "Amorphous Alloys: Their Properties and Applications", Takeshi Masumoto, Kazuaki Fukamichi, Agne Co., Ltd., (1981) Page 24 [Non-Patent Document 2] "Grain size and coercive force of Fe, Ni, and Co metals", Fumitaka Sato, Nobuyuki Tezuka, Tomoaki Sakurai, and Terunobu Miyazaki, Journal of the Magnetic Society of Japan 17, 886-891 (1993) Summary of the Invention [Problem to be solved by the invention]
[0009] The ribbon made of the fine crystal alloy was manufactured by once producing a ribbon made of amorphous by a rapid solidification process such as a single roll method or a double roll method, and then performing heat treatment. However, during this heat treatment, rarely, the crystal grains coarsened partially or over a wide area. In addition, when the workability was poor in the amorphous state before the heat treatment, problems such as cracks occurring during processing into the shape of the final product and a decrease in yield occurred.
[0010] The present invention has been made in view of the above circumstances, and has excellent soft magnetic properties Fe-based alloy ribbon and aims to provide the same. Further, the present invention aims to provide a Thin ribbon Fe-based alloy having excellent soft magnetic properties Fe-based amorphous alloy ribbon and excellent workability as a material therefor.
Means for Solving the Problems
[0011] The present invention has been made to solve the above problems, and the gist thereof is as follows.
[0012] [1] The composition formula is Fe 100-a-b-c-d-e B a Si b X c Cu d Z e and the balance consists of impurity elements. However, X in the composition formula is one or more elements selected from the group consisting of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, Z is N, one or more elements selected from the group consisting of P and S, and the composition ratios a, b, c, d, and e are in atomic %, respectively, 4 ≦ a ≦ 10 5 ≦ b ≦ 20, 1.0 ≦ c ≦ 3 0 < d ≦ 1 , 0.10 < e ≦ 3, 3 < c + e < 6 is satisfied, and the half-value width of the diffraction peak of the (110) plane of bcc-Fe in the X-ray diffraction pattern using Co-Kα rays as the X-ray source is 0.25 deg or more. The metal structure is made up of fine crystals with an average grain size of 60 nm or less.An Fe-based alloy, characterized in that Thin ribbon. 2 At the stage where the metal structure is an amorphous structure before heat treatment, the half-value width of the diffraction peak of the (110) plane of bcc-Fe in the X-ray diffraction pattern using Co-Kα rays as the X-ray source is 6° or more and 8° or less, The half-value width of the diffraction peak of the (110) plane of bcc-Fe at the stage where the metal structure is the fine crystal structure after heat treatment is 1 / 30 or more and 1 / 3 or less with respect to the half-value width of the diffraction peak of the (110) plane of bcc-Fe at the stage before heat treatment consisting of the amorphous structure, the law of nature, The heat treatment is a heat treatment in which the temperature rise rate is 5°C / min or more and 100°C / min or less, the soaking temperature is the first heat generation part peak temperature (Tp1) or more and the second heat generation part peak temperature (Tp2) or less measured by differential scanning calorimetry, and the soaking time is 0.5 hours or more and 6 hours or less. characterized in that [1] the Fe-based alloy according to Thin ribbon . 3 The composition formula is Fe 100-a-b-c-d-e B a Si b X c Cu d Z e and the balance consists of impurity elements. However, X in the composition formula is one or more elements selected from the group of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, Z is N, one or more elements selected from the group of P and S, and the composition ratios a, b, c, d, and e are in atomic %, respectively, 4 ≤ a ≤ 10 , 5 ≤ b ≤ 20, 1.0 ≤ c ≤ 3 , 0 < d ≤ 1 , 0.10 < e ≤ 3, 3 < c + e < 6 is satisfied, the metal structure consists of an amorphous structure, and the half-value width of the diffraction peak of the (110) plane of bcc-Fe in the X-ray diffraction pattern using Co-Kα rays as the X-ray source is 6° or more and 8° or less. An Fe-based amorphous alloy, Thin ribbon. 4 Heating rate: 5°C / min to 100°C / min. The soaking temperature is the first heat generating part peak temperature (T p1 ) or higher Second heat generating part peak temperature (T p2 ) or less, and the soaking time is 0.5 hours or more and 6 hours or less The half-width of the diffraction peak of the (110) plane of bcc-Fe when the metal structure is made into a fine crystal structure having an average grain size of 60 nm or less by heat treatment is in the range of 1 / 30 to 1 / 3 of the half-width of the diffraction peak of the (110) plane of bcc-Fe when the metal structure is made of the amorphous structure. [3] Fe-based amorphous alloys described in Thin ribbon . [ 5 ] Heating rate: 5°C / min to 100°C / min. The soaking temperature is the first heat generating part peak temperature (T p1 ) or higher Second heat generating part peak temperature (T p2 ) or less, and the soaking time is 0.5 hours or more and 6 hours or less The metal structure is characterized in that when the metal structure is transformed into a fine crystal structure with an average grain size of 60 nm or less by heat treatment, the half-width of the diffraction peak of the (110) plane of bcc-Fe is 0.25 deg or more. 4
[0023] The Fe-based amorphous alloy Thin ribbon. [ 6 The bending breaking diameter is 1 mm or less. Any one of items [3] to [5] 2. An Fe-based amorphous alloy ribbon according to claim 1. Effect of the Invention
[0013] According to the present invention, the magnetic material has excellent soft magnetic properties. Fe-based alloy ribbon can be provided. Furthermore, according to the present invention, a magnetron having excellent soft magnetic properties and which can be practically applied to products such as transformers is provided. Fe-based alloy ribbon According to the present invention, it is possible to provide an Fe-based alloy having excellent soft magnetic properties. Thin ribbon It is a material with excellent processability. Fe-based amorphous alloy ribbon can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present inventors have clarified for the first time the role of element X (Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, W) and element Z (C, N, P, S) in producing fine crystals in heat treatment when producing a fine crystal alloy having a fine crystal structure by heat treating an amorphous alloy, and have proposed the present invention by clarifying the optimal addition amount of these elements based on the results. In addition, the inventors have discovered that the soft magnetic properties of a fine crystal alloy can be further improved by specifying the fine crystal alloy using a new evaluation index obtained from the X-ray diffraction pattern.
[0015] It has been known that heat treatment of Fe-Si-B amorphous alloys results in crystallization. The crystallization process is said to proceed in two steps. In the first step, initial crystals (α-Fe) are generated as the heat treatment temperature increases. In the second step, the initial crystals grow discontinuously as the heat treatment temperature increases, and finally boron compounds are precipitated, completing the crystallization. If a small amount of Cu is added to the amorphous alloy, many fine crystals are generated in the first step. Furthermore, it is said that the fineness of the crystals is further promoted by adding elements such as Nb together with Cu to the amorphous alloy. In other words, it is known that the addition of elements such as Cu and Nb has the effect of producing fine crystals. In order to obtain a fine crystal alloy, it is necessary to control the heat treatment temperature so that the second step is not reached. This is because the finely precipitated crystals will become coarse if the second step is reached.
[0016] Therefore, it was necessary to first form an amorphous alloy and then heat-treat the Fe-Si-B-Cu-Nb-based fine crystal alloy containing Cu and Nb at a temperature between the first and second steps. However, as mentioned above, when heat-treating industrially, the crystal grains sometimes become coarse partially or over a wide area. The reason for this is thought to be that the temperature distribution in the furnace is large in industrial mass-production heat treatment furnaces, and there are places in the furnace or product where the furnace temperature becomes higher than the desired control temperature, and there are places where the furnace temperature rises to the temperature at which the second step occurs.
[0017] Therefore, the inventors of the present invention have conducted intensive research, thinking that by increasing the temperature difference between the first and second steps, it is possible to overcome the temperature difference in an industrial-scale heat treatment furnace and heat-treat an amorphous alloy within the temperature range between the first and second steps at all positions in the furnace. As a result, it has been found that the temperature difference between the first and second steps during heat treatment can be widened by previously adding one or more of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W in an optimal range to a ribbon made of an amorphous alloy. In other words, it has been revealed that it is possible to stably obtain a fine grain alloy and a ribbon thereof.
[0018] In addition, microcrystalline alloys are generally processed into a predetermined shape through processes such as cutting, lamination, and winding in the amorphous alloy state, and then heat treated to microcrystallize them. Therefore, if the amorphous alloy has low workability, the manufacturing yield of the final product may decrease. Therefore, the present inventors have found that by adding an appropriate amount of one or more of C, N, P, and S, the amorphous forming ability can be improved and an amorphous alloy with excellent workability can be stably produced.
[0019] Furthermore, the inventors evaluated the produced microcrystalline alloys and ribbons by X-ray diffraction and succeeded in clarifying this discovery by introducing a new evaluation index for X-ray diffraction patterns, thereby proposing the present invention.
[0020] That is, in the Fe-based alloy and ribbon according to the present invention, in an X-ray diffraction pattern using Co-Kα radiation as an X-ray source, the half-width of the diffraction peak of the bcc-Fe (110) plane at the stage when the metal structure is a fine crystal structure after heat treatment is preferably 1 / 30 or more and 1 / 3 or less of the half-width of the diffraction peak of the bcc-Fe (110) plane at the stage before heat treatment when the metal structure is an amorphous structure. By setting the ratio of the half-width of the diffraction peak of the bcc-Fe (110) plane before and after heat treatment in the X-ray diffraction pattern (hereinafter, sometimes referred to as the half-width ratio) within this range, it has been found that partial or wide-area coarsening of crystal grains that occurs when industrially producing a fine crystal alloy or ribbon by heat treatment can be prevented, and this conventional problem can be solved.
[0021] Here, by setting the half-width ratio to 1 / 30 or more, there is no risk of coarse crystal grains being generated partially or widely, and by setting it to 1 / 3 or less, a fine crystal structure can be generated over almost the entire area of the metal structure. Therefore, in order to obtain a preferable fine crystal grain structure, it is necessary to set this index range to 1 / 30 or more and 1 / 3 or less.
[0022] In the past, in order to improve the soft magnetic properties of Fe-based alloys, the average crystal grain size of the fine crystal structure was controlled to a size on the order of nanometers. However, the inventors have found that in order to more stably express the soft magnetic properties, it is not enough to control the crystal grain size alone, and it is necessary to prevent partial or wide-area coarsening of the crystal grains. After intensive research, they have found that the alloy is defined by the above-mentioned half-width ratio as an index of partial or wide-area coarsening of the crystal grains. It is not easy to directly detect partial coarsening of fine crystal grains on the order of nanometers in Fe-based alloys. Thus, the present invention is specified by the half-width ratio because the structure or properties cannot be directly determined or are almost impractical.
[0023] Furthermore, if the half-width of the diffraction peak of the (110) plane of bcc-Fe at the stage when the metal structure is amorphous is 6 deg or more, it is an amorphous alloy with excellent workability and can be processed into the desired shape with good yield. There is no particular upper limit to this half-width, but it is thought that the upper limit is 8 deg.
[0024] According to the present invention, by adding Cu to an Fe-Si-B amorphous alloy and pre-adding one or more of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W in an optimal range, and then heat-treating the alloy at a temperature between the first and second crystallization steps, it is possible to set the half-width ratio to a range of 1 / 30 to 1 / 3. Also, by adding an appropriate amount of one or more of C, N, P, and S, it is possible to set the half-width of the diffraction peak of the (110) plane of bcc-Fe in the amorphous state before heat-treatment to 6 deg or more, thereby improving the workability.
[0025] The Fe-based alloy and Fe-based amorphous alloy according to the present invention will be described in detail below.
[0026] (Composition of Fe-based alloys and Fe-based amorphous alloys) The Fe-based amorphous alloy and the Fe-based alloy of the present embodiment are 、 In an alloy containing B, Si, X, Cu and Z (wherein X is one or more of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo and W, and Z is one or more of C, N, P and S), the problems of poor workability in an amorphous state and partial or widespread coarsening of crystal grains during heat treatment have been solved by making the alloy into the following composition formula (I). The composition formula (II) is preferable, and the composition formula (III) is more preferable.
[0027] Composition formula (I): Fe 100-a-b-c-d-e B a S b X c Cu d Z eIt is represented by and the remainder consists of impurity elements. However, X in the above composition formula is one or more elements selected from the group of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, Z is one or more elements selected from the group of C, N, P, and S, and the composition ratios a, b, c, d, and e are in atomic percentages respectively, satisfying 4 ≦ a ≦ 20, 5 ≦ b ≦ 20, 1 ≦ c ≦ 5, 0 < d ≦ 3, 0.1 < e ≦ 3, and 1.1 < c + e < 6.
[0028] Composition formula (II): Fe 100-a-b-c-d-e B a Si b X c Cu d Z e It is represented by and the remainder consists of impurity elements. However, X in the above composition formula is one or more elements selected from the group of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, Z is one or more elements selected from the group of C, N, P, and S, and the composition ratios a, b, c, d, and e are in atomic percentages respectively, satisfying 4 ≦ a ≦ 20, 5 ≦ b ≦ 20, 1 ≦ c ≦ 5, 0 < d ≦ 3, 1 < e ≦ 3, and 2 < c + e < 6, and Fe is less than 79 atomic %.
[0029] Composition formula (III): Fe 100-a-b-c-d-e B a Si b X c Cu d Z e It is represented by and the remainder consists of impurity elements. However, X in the above composition formula is one or more elements selected from the group of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, Z is one or more elements selected from the group of C, N, P, and S, and the composition ratios a, b, c, d, and e are in atomic percentages respectively, satisfying 4 ≦ a ≦ 20, 5 ≦ b ≦ 20, 1 ≦ c ≦ 3, 0 < d ≦ 3, 2 < e ≦ 3, and 3 < c + e < 6, and Fe is less than 79 atomic %.
[0030] B is an element that enhances the amorphous-forming ability, and the composition ratio a of B is 4≦a≦20 in atomic %. If the composition ratio a of B is less than 4 atomic %, the amorphous-forming ability deteriorates, which is not preferable, and if it exceeds 20 atomic %, it will lead to a decrease in saturation magnetic flux density, which is also not preferable. Therefore, the composition ratio a of B is 4≦a≦20. A more preferable range of a is 5≦a≦10, and an even more preferable range of a is 5≦a≦8.
[0031] Si is an element that enhances the amorphous forming ability, and the composition ratio b of Si is 5≦b≦20 in atomic %. Si also has the effect of improving interlayer insulation when stacked as a magnetic core or the like and used by segregating as an oxide on the alloy surface. If Si is less than 5 atomic %, the amorphous forming ability becomes insufficient. If the composition ratio b of Si exceeds 20 atomic %, it is not preferable because it leads to a decrease in saturation magnetic flux density. Therefore, the composition ratio b of Si is 5≦b≦20 in atomic %. A more preferable range of the composition ratio b is 8≦b≦16, and an even more preferable range of the composition ratio b is 12≦b≦16, and it may even be 12.5≦b≦15.5.
[0032] The X element is one or more of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W. The X element has the effect of widening the temperature difference between the first and second steps during heat treatment, and can stably obtain a fine grain alloy and a thin strip thereof even in an industrial-scale heat treatment furnace. One or more of Nb, V, Ta, Cr, Mo, and W are more preferable, and one or more of Nb, V, W, and Cr are even more preferable.
[0033] The composition ratio c of the X element is 1≦c≦5 in atomic %. By including the X element, the effect of widening the temperature difference between the first step and the second step during the heat treatment can be obtained, but it is preferable to include the X element at 1 atomic % or more because a sufficient effect can be obtained. If the composition ratio c of the X element exceeds 5 atomic %, it is not preferable because it leads to a decrease in the saturation magnetic flux density. More preferably, the composition ratio c of the X element is 1≦c≦4, and more preferably, 1≦c≦3.
[0034] Cu acts as a nucleation site during microcrystallization and has the effect of uniformly forming fine crystal grains. The composition ratio d of Cu is 0 < d ≤ 3. Cu is essential for microcrystallization, but when it exceeds 3 atomic%, the amorphous forming ability decreases, making it difficult to manufacture continuous amorphous alloy ribbons. A more preferable composition ratio d of Cu is 0 < d ≤ 2, and even more preferably 0.5 < d ≤ 1.
[0035] The Z element is one or more elements of C, N, P, and S. These Z elements have the effect of improving the amorphous forming ability and can improve the workability in the amorphous state. In particular, one or more of C and P are preferable. The composition ratio e of the Z element is 0.1 < e ≤ 3. When the composition ratio e of the Z element exceeds 3 atomic%, it causes a decrease in the saturation magnetic flux density, which is not preferable. Also, when the composition ratio e of the Z element is 0.1 atomic% or less, the amorphous forming ability is not sufficient. A more preferable composition ratio e of the Z element is 1 < e ≤ 3, and even more preferably, the composition ratio e of the Z element is 2 < e ≤ 3.
[0036] As described above, the X element (one or more of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W) has the effect of widening the temperature difference between the first step and the second step during heat treatment, and the Z element (one or more of C, N, P, and S) has the effect of improving the amorphous forming ability and can improve the workability. However, as a result of the inventors' intensive research, it has been found that by adjusting the sum (c + e) of the composition ratio c of the X element and the composition ratio e of the Z element, these effects can be achieved simultaneously. Specifically, the sum of the X element and the Z element is preferably 1.1 < c + e < 6, more preferably 2 < c + e < 6, and even more preferably 3 < c + e < 6.
[0037] The balance in the Fe-based amorphous alloy or Fe-based alloy according to the present invention is Fe and impurity elements. Fe is more preferably 79 atomic% or less. By restricting the content of Fe, the content of other additive elements can be relatively increased, and the soft magnetic properties and workability can be further enhanced. In particular, the amorphous forming ability is improved and the castability is improved, so that casting can be stably performed by the rapid cooling method.
[0038] The Fe-based amorphous alloy or Fe-based alloy according to the present invention may contain impurities contained in steel materials as impurity elements. For example, C, N, P, S, O, etc. may be contained as impurities. C, P, and S may be contained as Z elements within the above-mentioned predetermined amount range, and may be contained in trace amounts as impurity elements.
[0039] (Metal structure of Fe-based amorphous alloy) Next, the metal structure of the Fe-based amorphous alloy will be described. The metal structure of Fe-based amorphous alloys is amorphous. If there is a crystalline structure in part of the metal structure, there is a risk that a coarse crystalline grain structure will form during subsequent heat treatment. Therefore, the entire metal structure must be amorphous.
[0040] In addition, the Fe-based amorphous alloy must have a half-width of 6 degrees to 8 degrees for the diffraction peak of the bcc-Fe (110) plane in the X-ray diffraction pattern using Co-Kα radiation as the X-ray source. If the half-width is less than 6 degrees, the workability of the Fe-based amorphous alloy cannot be improved. On the other hand, since the metal structure is amorphous, there is no need to specify an upper limit for the half-width, but if an upper limit must be specified, a value of 8 degrees or less is sufficient.
[0041] The Fe-based amorphous alloy of this embodiment may be a thin strip having a thickness of 10 μm or more and 100 μm or less and a width of 10 mm or more.
[0042] The ribbon made of the Fe-based amorphous alloy preferably has a bending fracture diameter of 2 mm or less, more preferably 1 mm or less. In the case of the above composition formula (III), a bending fracture diameter of 1 mm or less is easily obtained, and in the case of the above composition formula (I) or (II), a bending fracture diameter of 2 mm or less is easily obtained. The bending fracture radius is measured in accordance with the bending test method for metallic materials of JIS Z 2248:2006, by placing a ribbon made of the Fe-based amorphous alloy on a bending tester, pressing both ends of the test piece against each other until they come into close contact, and measuring the diameter of the test piece at the time of breakage (bending fracture diameter).
[0043] The ribbon made of the Fe-based amorphous alloy according to the present embodiment has a small bending fracture diameter and excellent processability. Therefore, when transformers, choke coils, noise suppression products, etc. are manufactured, the ribbon made of the Fe-based amorphous alloy can be incorporated as a component material of these products without being damaged. Then, by performing heat treatment under appropriate conditions, it becomes possible to manufacture products such as transformers equipped with an Fe-based alloy having excellent soft magnetic properties.
[0044] (Metal structure of Fe-based alloys) Next, the metal structure of the Fe-based alloy will be described. The metal structure of the Fe-based alloy of this embodiment can be obtained by heat treating the Fe-based amorphous alloy of this embodiment.
[0045] In the Fe-based alloy of this embodiment, the half-width of the diffraction peak of the (110) plane of bcc-Fe in the X-ray diffraction pattern using Co-Kα radiation as the X-ray source is 0.25 deg or more. It is preferably 0.4 deg or more. When the average crystal grain size is calculated using the Scherrer formula described later, the average crystal grain size is 60 nm or less when the half-width is 0.25 deg or more, and the average crystal grain size is 30 nm or less when the half-width is 0.4 deg or more. An Fe-based alloy having such a half-width exhibits excellent soft magnetic properties.
[0046] The metal structure of the Fe-based amorphous alloy is preferably a fine crystal structure with a crystal grain size of 60 nm or less, more preferably 30 nm or less. By making such a fine crystal structure, the Fe-based alloy exhibits excellent soft magnetic properties.
[0047] In addition, since the Fe-based alloy of this embodiment has any one of the compositions of the above composition formulas (I) to (III), the upper and lower limits of the soaking temperature in the heat treatment for obtaining a crystal grain size of 60 nm or less are within a wide range of 50° C. or more, which reduces the rate of defective products caused by temperature variations in the heat treatment device, thereby improving the product yield.
[0048] In addition, in an Fe-based alloy, in an X-ray diffraction pattern using Co-Kα radiation as an X-ray source, the half-width of the diffraction peak of the bcc-Fe (110) plane when the metal structure is a fine crystal structure after heat treatment is preferably 1 / 30 to 1 / 3 of the half-width of the diffraction peak of the bcc-Fe (110) plane when the metal structure is an amorphous structure before heat treatment. By setting the ratio of the half-width of the diffraction peak of the bcc-Fe (110) plane in the X-ray diffraction pattern before and after heat treatment (half-width ratio) in this range, partial or wide-area coarsening of crystal grains that occurs when industrially producing a fine crystal alloy or ribbon by heat treatment can be prevented.
[0049] The Fe-based alloy of this embodiment may be a thin strip having a thickness of 10 μm or more and 100 μm or less and a width of 10 mm or more.
[0050] The half-width of the diffraction peak of the (110) plane of bcc-Fe in the Fe-based amorphous alloy and Fe-based alloy of this embodiment can be obtained by performing X-ray diffraction measurement on these alloys to obtain an X-ray diffraction pattern. The X-ray source for the X-ray diffraction measurement is Co-Kα (wavelength λ=1.7902 Å), and the scan range is 2θ=10 deg or more and 120 deg or less. The diffraction peak of the (110) plane of bcc-Fe is identified from the X-ray diffraction pattern, and the half-width of the diffraction peak is obtained.
[0051] The average crystal grain size of the metal structure of Fe-based alloys can be calculated by introducing the half-width of the diffraction peak of the (110) plane of bcc-Fe into the Scherrer formula. The Scherrer formula is expressed by the following formula. In the Scherrer formula, K is the Scherrer constant (0.94), λ is the wavelength of the X-ray source (1.7902 Å), β is the half-width of the diffraction peak, θ is the diffraction angle of the diffraction peak of the (110) plane, and D is the average crystal grain size. Note that the half-width measured from the diffraction peak includes peak broadening due to the measuring equipment, so the value obtained by subtracting the peak broadening (0.07 deg) from the half-width is used as the half-width β.
[0052] D=Kλ / βcosθ …(Scherrer's formula)
[0053] Furthermore, the heat treatment conditions for determining the half-width ratio are: heating rate: 5 to 100°C / min; soaking temperature: first heat generation part peak temperature (T p1 ) or higher, the second heat generating part peak temperature (T p2 ) Hereinafter, the soaking time is in the range of 0.5 to 6 hours. Within this range of heat treatment conditions, the half-width of bcc-Fe in the Fe-based alloy will be a substantially constant value, so the heat treatment conditions for measuring the half-width may be arbitrarily selected within the above range. When heat treatment is performed within the above range, the half-width ratio and the half-width of the (110) plane of Fe after heat treatment should fall within the above range.
[0054] Next, a method for producing the Fe-based amorphous alloy and the Fe-based alloy of this embodiment will be described.
[0055] The Fe-based amorphous alloy of this embodiment can be produced by quenching a molten alloy having the above composition formula, or by subjecting the Fe-based amorphous alloy to a heat treatment under appropriate conditions.
[0056] In this embodiment, the amorphous alloy can be obtained in the form of a ribbon by the single roll method or the twin roll method. The rolls used in these roll methods are made of metal, and the alloy can be rapidly solidified by rotating the rolls at high speed and colliding the molten alloy with the roll surface or the roll inner surface. Single roll devices include centrifugal quenching devices that use the inner wall of a drum, devices that use an endless type belt, and improved versions of these devices that are equipped with auxiliary rolls or roll surface temperature control devices, as well as casting devices that operate under reduced pressure, in vacuum, or in inert gas.
[0057] Although there are no particular limitations on the dimensions of the ribbon, such as its thickness and width, the ribbon thickness is preferably, for example, 10 μm or more and 100 μm or less, and the ribbon width is preferably 10 mm or more.
[0058] The Fe-based amorphous alloy of this embodiment can be in the form of powder in addition to the ribbon. In this case, a method can be adopted in which the molten alloy or droplets of the molten alloy are ejected at high speed from a nozzle of a crucible filled with the molten alloy of the above composition into a rotating roll or a liquid such as cooling water, thereby rapidly solidifying the alloy, and the ribbon can be cut and crushed to obtain powder.
[0059] Next, the heat treatment conditions will be described. Since crystallization may start before the soaking temperature is reached, the heating rate should be fast, at least 5°C / min, and preferably at least 10°C / min. By raising the heating rate to 5°C / min or more, a uniform fine crystal structure with an average grain size of 60 nm or less can be formed. The higher the heating rate, the better, but to make the temperature distribution in the heat treatment device uniform, the heating rate should be 100°C / min or less.
[0060] The soaking temperature is the first heat generation peak temperature (T p1 ) or higher, the second heat generating part peak temperature (T p2 ) or less. In differential scanning calorimetry, if the heating rate is within the range of 10°C to 40°C / min, a constant peak temperature can be obtained. In practice, it is set to 10°C / min. The first heat generation part peak temperature (T p1 ) is the peak temperature of the first exothermic peak observed in the DSC curve after the start of the temperature rise. The second exothermic peak temperature (T p2 ) is the first heat generation peak temperature (T p1 ) in the temperature range higher than the first heat generation peak temperature (T p1 ) is the peak temperature of the exothermic peak that appears next to the exothermic peak of T p1 More than T p2 By performing heat treatment at the soaking temperature below, the problem of crystal grains becoming coarse partially or widely can be solved, and an Fe-based alloy can be obtained stably. p1 and T p2 The temperature difference can be more than 50℃.
[0061] The soaking time is preferably in the range of 0.5 hours to 6 hours. By setting the soaking time to 0.5 hours or more, a fine crystal structure can be formed throughout the metal structure. Furthermore, by setting the soaking time to 6 hours or less, coarsening of fine crystal grains can be prevented.
[0062] Heat treatment equipment includes electric heating furnaces, infrared lamp heating furnaces, laser heating equipment, etc., and Fe-based alloys can be obtained using any of these equipment. Heat treatment can be performed in air, vacuum, in an inert gas (Ar, nitrogen, He, etc.), or in water vapor, but it is particularly preferable to perform it in an inert gas.
[0063] In addition, in this embodiment, when producing an Fe-based alloy by heat treating an Fe-based amorphous alloy, the temperature difference between the upper and lower limits of the soaking temperature range in which the crystal grain size is 60 nm or less is 50° C. or more, preferably 60° C. or more, and more preferably 80° C. or more. By making the temperature difference in the soaking temperature range 50° C. or more, it becomes possible to overcome the temperature difference in an industrial-scale heat treatment furnace and stably produce an Fe-based alloy having crystal grains with a grain size of 60 nm or less when the amorphous alloy is heat treated within the temperature range between the first step and the second step at all positions in the furnace. EXAMPLES
[0064] Examples will now be described. The alloys with the various components shown in Table 1 were melted in an argon atmosphere, and then rapidly cooled and cast in a single-roll apparatus to produce ribbons of Fe-based amorphous alloys. The casting atmosphere was air. The single-roll apparatus used consisted of a copper alloy cooling roll with a diameter of 300 mm, a high-frequency power source for melting the samples, and a quartz crucible with a slot nozzle at its tip. In this experiment, a slot nozzle with a length of 10 mm and a width of 0.6 mm was used. The peripheral speed of the cooling roll was 24 m / sec. As a result, the thickness of the obtained ribbon was about 20 μm, the width was 10 mm because it depended on the length of the slot nozzle, and the length was about 100 m.
[0065] The first heat generation peak temperature (T p1 ) and the second heat generation peak temperature (T p2 The temperature rise rate for the differential scanning calorimetry was 10° C. / min. The first heat generation peak temperature (T p1 ) was the peak temperature of the first exothermic peak observed in the DSC curve after the start of the temperature rise. The second exothermic peak temperature (T p2 ) is the first heat generation peak temperature (T p1 ) in the temperature range higher than the first heat generation peak temperature (T p1 The peak temperature was determined as the peak temperature of the exothermic peak that appeared next to the exothermic peak of the first heat generation.
[0066] The amorphous alloy was then heat-treated under the conditions shown in Table 1 to form a fine crystal structure, thereby producing an Fe-based alloy. p1 ) or higher, the second heat generating part peak temperature (T p2 ) or less. Table 1 shows the first heat generation part peak temperature (T p1 ) and the second heat generation peak temperature (T p2 ) are also shown.
[0067] X-ray diffraction measurements were performed on the obtained Fe-based amorphous alloy and Fe-based alloy to obtain X-ray diffraction patterns. Then, the half-width of the diffraction peak of the Fe (110) plane on the X-ray diffraction pattern of each alloy was measured. In addition, the half-width ratio was calculated from the half-width of the diffraction peak of the Fe (110) plane of the Fe-based amorphous alloy before heat treatment and the half-width of the diffraction peak of the Fe (110) plane of the Fe-based alloy. The X-ray source for the X-ray diffraction measurement was Co-Kα (wavelength λ = 1.7902 Å), and the scan range was 2θ = 10 deg or more and 120 deg or less. The diffraction peak of the bcc-Fe (110) plane was identified from the X-ray diffraction pattern, and the half-width of the diffraction peak was calculated. The results are shown in Table 2.
[0068] The average grain size of the Fe-based alloy metal structure was calculated from the half-width of the diffraction peak of the (110) plane of Fe in the Fe-based alloy. The average grain size was calculated by introducing the half-width of the diffraction peak of the (110) plane of bcc-Fe into the Scherrer formula. The Scherrer formula is expressed by the following formula. In the Scherrer formula, K is the Scherrer constant (0.94), λ is the wavelength of the X-ray source (1.7902 Å), β is the half-width of the diffraction peak, θ is the diffraction angle of the diffraction peak of the (110) plane, and D is the average grain size. Note that the half-width measured from the diffraction peak includes the peak broadening caused by the measuring device, so the value obtained by subtracting the peak broadening (0.07 deg) from the half-width was used as the half-width β. The results are shown in Table 2.
[0069] D=Kλ / βcosθ …(Scherrer's formula)
[0070] The soaking temperature range in which the crystal grain size becomes 60 nm or less was determined as follows. A 10 mm × 10 mm sample was prepared from an Fe-based amorphous alloy ribbon that was quenched and cast using a single roll device, and the sample was heated at a heating rate of 10°C / min and held at a temperature equal to or less than the first heat generation peak temperature (T p1 ) to the second heat generating part peak temperature (T p2 ) in 10°C increments, and heat treatment was performed in a nitrogen atmosphere. X-ray diffraction measurements were performed on the heat-treated samples to measure the half-width from the X-ray diffraction pattern, and the average crystal grain size was calculated using the Scherrer equation, and the soaking temperature range at which the crystal grain size was 60 nm or less was determined.
[0071] A toroidal core with an inner diameter of 15 mm, an outer diameter of 20 mm, and a width of 10 mm was made from the Fe-based alloy ribbon, and its DC magnetic properties were evaluated. The initial permeability and coercive force Hc measured at a maximum magnetic field of 800 A / m, and the magnetic flux density at saturation when the magnetic field was increased (saturation magnetic flux density) are shown in Table 3. Samples with an initial permeability of 50,000 or more, a coercive force Hc of 1.0 A / m or less, and a saturation magnetic flux density of 1.0 T or more were deemed to have excellent soft magnetic properties and passed the test.
[0072] Furthermore, the bending fracture diameter of the Fe-based amorphous alloy was measured. The bending fracture radius was measured in accordance with the bending test method for metallic materials of JIS Z 2248:2006, in which a thin ribbon made of an Fe-based amorphous alloy was placed on a bending tester, and the bending fracture diameter at the time of breakage was measured. The results are shown in Table 3.
[0073] As shown in Tables 1 to 3, Examples 1 to 8 (Examples 1, 3, 4, 6, and 7 are reference examples) The Fe-based amorphous alloy had a bending fracture radius of 1 mm or less, was capable of close bending, and had excellent workability. It could also be used as a material for Fe-based alloys with excellent soft magnetic properties. In addition, as shown in Tables 1 to 3, Examples 1 to 8 (Examples 1, 3, 4, 6, and 7 are reference examples) The Fe-based alloy had high initial permeability and saturation magnetic flux density, low coercive force, and excellent soft magnetic properties.
[0074] In Comparative Example 1 and Comparative Example 2, the composition ratio of the X element was outside the range of the present invention, so that the half-width of the peak of the Fe(110) plane after the heat treatment of the quenched Fe-based amorphous alloy was less than 0.25 deg, the metal structure became a coarse crystal structure, and the soft magnetic properties were insufficient. Therefore, the Fe-based amorphous alloys of Comparative Example 1 and Comparative Example 2 could not be used as materials for Fe-based alloys with excellent soft magnetic properties.
[0075] In Comparative Example 3 and Comparative Example 4, the composition ratio of the Z element was outside the range of the present invention, so the half-width of the diffraction peak of the Fe (110) plane of the Fe-based amorphous alloy before heat treatment was less than 6 deg., the bending fracture radius was more than 1 mm, and the workability was reduced. Therefore, even if the Fe-based alloys of Comparative Example 3 and Comparative Example 4 were applied to transformers, choke coils, noise countermeasure products, etc., it was predicted that the yield during the manufacture of these products such as transformers would be significantly reduced due to the low workability of the Fe-based amorphous alloy, which is the material. Therefore, the Fe-based alloys of Comparative Example 3 and Comparative Example 4 could not be said to be practical.
[0076] In Comparative Example 5, the composition ratio a of B was less than 4 atomic %, and the amorphous forming ability was insufficient. As a result of X-ray diffraction measurement of a ribbon that was quenched and cast using a single roll device, a diffraction peak of the (110) plane of Fe was clearly present. The metal structure of the ribbon after quenching was a coarse crystal structure, and an amorphous alloy could not be obtained. Therefore, it was not possible to measure the peak temperature by differential scanning calorimetry, to microcrystallize by heat treatment, or to evaluate the magnetic properties after heat treatment, and therefore "-" was entered in the columns of Tables 1 to 3. Therefore, the alloy after quenching in Comparative Example 5 was not usable as a material for an Fe-based alloy.
[0077] In Comparative Example 6, the composition ratio a of B exceeded 20 atomic %, and the saturation magnetic flux density of the alloy after heat treatment was less than 1.0 T, resulting in insufficient soft magnetic properties. Therefore, the Fe-based amorphous alloy of Comparative Example 6 cannot be used as a material for an Fe-based alloy with excellent soft magnetic properties, and the Fe-based alloy of Comparative Example 6 also had insufficient soft magnetic properties.
[0078] In Comparative Example 7, the composition ratio b of Si was less than 5 atomic %, and as a result of X-ray diffraction measurement of a ribbon cast by quenching in a single roll apparatus, a diffraction peak of the (110) plane of Fe was clearly present. The metal structure of the ribbon after quenching was a coarse crystalline structure, and an amorphous alloy could not be obtained. Therefore, it was not possible to measure the peak temperature by differential scanning calorimetry, to microcrystallize by heat treatment, or to evaluate the magnetic properties after heat treatment, and therefore "-" was entered in the columns of Tables 1 to 3. Therefore, the alloy after quenching in Comparative Example 7 was not usable as a material for an Fe-based alloy.
[0079] In Comparative Example 8, the composition ratio a of Si exceeded 20 atomic %, and the saturation magnetic flux density of the alloy after heat treatment was less than 1.0 T, resulting in insufficient soft magnetic properties. Therefore, the Fe-based amorphous alloy of Comparative Example 8 cannot be used as a material for an Fe-based alloy with excellent soft magnetic properties, and the Fe-based alloy of Comparative Example 8 also had insufficient soft magnetic properties.
[0080] Comparative Example 9 is an example that does not contain Cu, and the average crystal grain size of the Fe-based alloy made from this material exceeded 60 nm, resulting in insufficient soft magnetic properties, and therefore it could not be used as a material for an Fe-based alloy with excellent soft magnetic properties.
[0081] In Comparative Example 10, the composition ratio d of Cu exceeded 3 atomic %, and as a result of X-ray diffraction measurement of a ribbon cast by quenching in a single roll apparatus, a diffraction peak of the (110) plane of Fe was clearly present. The metal structure of the ribbon after quenching was a coarse crystalline structure, and an amorphous alloy could not be obtained. Therefore, it was not possible to measure the peak temperature by differential scanning calorimetry, to microcrystallize by heat treatment, or to evaluate the magnetic properties after heat treatment, and therefore "-" was entered in the columns of Tables 1 to 3. Therefore, the alloy after quenching in Comparative Example 10 could not be used as a material for an Fe-based alloy.
[0082] [Table 1]
[0083] [Table 2]
[0084] [Table 3]
Claims
1. The composition formula is Fe 100-a-b-c-d-e B a S b X c Cu d Z e and the remainder being impurity elements, wherein X in the composition formula is one or more elements selected from the group consisting of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, and Z is one or more elements selected from the group consisting of N, P, and S, and the composition ratios a, b, c, d, and e each satisfy, in atomic %, 4≦a≦10, 5≦b≦20, 1.0≦c≦3, 0<d≦1, 0.10<e≦3, and 3<c+e<6, The half-width of the diffraction peak of the (110) plane of bcc-Fe in an X-ray diffraction pattern using Co-Kα radiation as an X-ray source is 0.25 deg or more; An Fe-based alloy ribbon, characterized in that the metal structure is made of a fine crystal structure having an average grain size of 60 nm or less.
2. the half-width of a diffraction peak of a bcc-Fe (110) plane in an X-ray diffraction pattern using Co-Kα radiation as an X-ray source at a stage when the metal structure is an amorphous structure before heat treatment is 6 deg or more and 8 deg or less; the half-width of a diffraction peak of the (110) plane of bcc-Fe at a stage in which the metal structure is made of the fine crystal structure after the heat treatment is 1 / 30 or more and 1 / 3 or less of the half-width of a diffraction peak of the (110) plane of bcc-Fe at a stage in which the metal structure is made of the amorphous structure before the heat treatment; The Fe-based alloy ribbon according to claim 1, characterized in that the heat treatment is a heat treatment having a temperature rise rate of 5°C / min or more and 100°C / min or less, a soaking temperature of a first heat generation portion peak temperature (Tp1) or more and a second heat generation portion peak temperature (Tp2) or less measured by differential scanning calorimetry, and a soaking time of 0.5 hours or more and 6 hours or less.
3. The composition formula is Fe 100-a-b-c-d-e B a S b X c Cu d Z e and the remainder being impurity elements, wherein X in the composition formula is one or more elements selected from the group consisting of Nb, Ti, Zr, Hf, V, Ta, Cr, Mo, and W, and Z is one or more elements selected from the group consisting of N, P, and S, and the composition ratios a, b, c, d, and e each satisfy, in atomic %, 4≦a≦10, 5≦b≦20, 1.0≦c≦3, 0<d≦1, 0.10<e≦3, and 3<c+e<6, The metal structure is amorphous. An Fe-based amorphous alloy ribbon, characterized in that the half-width of a diffraction peak of a (110) plane of bcc-Fe in an X-ray diffraction pattern using Co-Kα rays as an X-ray source is 6 deg or more and 8 deg or less.
4. An Fe-based amorphous alloy ribbon as described in claim 3, characterized in that the half-width of the diffraction peak of the (110) plane of bcc-Fe when the metal structure is converted into a fine crystal structure having an average grain size of 60 nm or less by heat treatment with a heating rate of 5°C / min or more and 100°C / min or less, a soaking temperature of not less than the first heating part peak temperature (T p1 ) and not more than the second heating part peak temperature (T p2 ) measured by differential scanning calorimetry, and a soaking time of not less than 0.5 hours and not more than 6 hours is in the range of 1 / 30 to 1 / 3 of the half-width of the diffraction peak of the (110) plane of bcc-Fe when the metal structure is composed of the amorphous structure.
5. An Fe-based amorphous alloy ribbon as described in claim 4, characterized in that the half-width of the diffraction peak of the (110) plane of bcc-Fe is 0.25 deg or more when the metal structure is converted into a fine crystal structure having an average grain size of 60 nm or less by heat treatment with a heating rate of 5°C / min or more and 100°C / min or less, a soaking temperature of not less than the first heating part peak temperature (T p1 ) and not more than the second heating part peak temperature (T p2 ) measured by differential scanning calorimetry, and a soaking time of not less than 0.5 hours and not more than 6 hours.
6. 6. The Fe-based amorphous alloy ribbon according to claim 3, wherein a bending fracture diameter is 1 mm or less.
Citation Information
Patent Citations
JP17、886-891
Fe-base soft magnetic alloy and its production
JP1989079342A
Soft-magnetic alloy having high saturation magnetic flux density
JP1989156451A
Amorphous alloy thin strip, nano-crystalline soft magnetic alloy, and magnetic core composed of nano-crystalline soft magnetic alloy
JP2007182594A
Powder magnetic core and method for manufacturing the same
JP2011216839A